Study of The Form and Meaning of Communication Batik Klitikan Sintok Kedah Malaysia - Jati Widagdo (Wimba : Jurnal Komunikasi Visual, 2021)
Batik Sintok is one of the new icons from the Kedah, Malaysia. It already has a patent, and has nine motifs, one of which is the Klitikan Sintok motif. Klitikan Sintok has a "distinctive" characteristic that lies in itsmotive because it is the result of plant elements living from the neighborhood of Sintok, namely the Sintoktree, which is styled in such a way as to form the structure of the Sintok motif. The purpose of this research isto determine and describe the embodiment of the Klitikan Sintok batik motif to find out and describe themeaning of the Klitikan Sintok motif. Research using qualitative methods described descriptively. Datacollection was carried out with observation, documentation obtained during the study, as well as with relevantliterature and using Rolan Bartes' theory to dissect the meaning of Klitikan Sintok's motives. Keywords: batik, Klitikan Sintok motif, shape, meaning